Analysis of Information Security Awareness within Users’ Preference, Practice and Knowledge - T. T. Ting; Z. H. Eu; S. B. Lim; K. S. Chong (Journal of Advanced Research in Computing and Applications, 2023)
As the technology keeps on improving, the Internet is becoming essential in daily living. Online shopping, social media, e-banking are among the common activities carried out in the Internet which involved private information storage and sharing. Therefore, information security issues arise as one of the main concerns among the Internet users. Experts believed that the main cause of security issue is the reckless behaviour of user such as ignorance, lack of awareness, and resistance. This research is carried out to explore the Internet users’ security awareness in Malaysia in terms of users’ preference, practice and knowledge. It was found that there is a difference between user’s preference, practice and knowledge regarding information security countermeasures. It is crucial to explore the user’s security awareness in order to provide better solutions to assist users in securing their private information and thus reducing the Internet threats.